Totally Laparoscopic Total Gastrectomy for Gastric Cancer at a Single Institutional Experience and Changes in Technique of Esophagojejunostomy - Umemura, Akira (Indian J Surg, 2016)
The totally laparoscopic total gastrectomy (TLTG) for gastric cancer has not gained widespread acceptance due to its technical difficulties, especially with the intracorporeal esophagojejunostomy (IEJS). Various modified procedures for the IEJS have been devised, but an optimal method has not yet been standardized. A total of 32 consecutive patients (23 men and 9 women) underwent TLTGs for gastric cancer, between December of 2009 and December of 2014 at the Iwate Medical University Hospital, and were enrolled in this study. Here, we report our institution’s experience with TLTGs, with changes in the IEJS. The study participants had a mean age of 66.8 years and a body mass index of 22.8 kg/m2. The mean operation time and blood loss were 356.1 min and 61.2 mL, respectively. According to the IEJS, there were 6 circular stapler (CS) (single and double stapling techniques) and 26 linear stapler (LS) (overlap technique and functional end-to-end anastomosis) procedures performed. Two patients, who had undergone IEJS by double stapling technique, developed anastomotic stenosis and required endoscopic balloon dilatations of the anastomotic sites. Therefore, we changed to LS to secure the abundant anastomotic diameter. In our institute, some problematic complications in the IEJS procedure occurred at the introduction of the TLTG. We have overcome these complications by changing and standardizing the IEJS techniques, and by cultivating the laparoscopic techniques.